2018
DOI: 10.1021/acs.orglett.7b03906
|View full text |Cite
|
Sign up to set email alerts
|

Formal (4 + 1)-Addition of Allenoates to o-Quinone Methides

Abstract: The first (4 + 1)-annulation of o-quinone methides with α-branched allenoates as C1 synthons has been developed. This operationally simple protocol gives access to highly functionalized dihydrobenzofurans in an unprecedented fashion with excellent diastereoselectivities and high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…Two years ago we reported the first highly enantioselective synthesis of compounds 1 by reacting preformed chiral ammonium ylides with in situ formed o ‐QMs 2 . More recently we found that the highly functionalized allenoates 4 can undergo a very unique (and up to then unprecedented) formal [4+1]‐cyclization with acceptors 2 in the presence of a stoichiometric amount of PPh 3 (Scheme C) . The (unexpected) outcome of this reaction was in sharp contrast to other previously described reactions between o ‐QMs 2 and (differently substituted) allenoates, which all resulted in formal [4+2]‐annulations .…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Two years ago we reported the first highly enantioselective synthesis of compounds 1 by reacting preformed chiral ammonium ylides with in situ formed o ‐QMs 2 . More recently we found that the highly functionalized allenoates 4 can undergo a very unique (and up to then unprecedented) formal [4+1]‐cyclization with acceptors 2 in the presence of a stoichiometric amount of PPh 3 (Scheme C) . The (unexpected) outcome of this reaction was in sharp contrast to other previously described reactions between o ‐QMs 2 and (differently substituted) allenoates, which all resulted in formal [4+2]‐annulations .…”
Section: Introductionmentioning
confidence: 74%
“…The (unexpected) outcome of this reaction was in sharp contrast to other previously described reactions between o ‐QMs 2 and (differently substituted) allenoates, which all resulted in formal [4+2]‐annulations . Unfortunately however, we were only able to carry out this reaction in racemic manner, as even the use of a stoichiometric amount of different commonly used chiral phosphine catalysts gave low yields and poor enantioselectivities only . In especially we found that the in situ formed o ‐QMs 2 decomposed rather rapidly under the previously developed reaction conditions, thus making a catalytic approach difficult.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations